Metabolic Engineering of Lactobacillus helveticus CNRZ32 for Production of Pure l-(+)-Lactic Acid - Kylä-Nikkilä, Kari (American Society for Microbiology, 2000)
Expression of d-(−)-lactate dehydrogenase (d-LDH) and l-(+)-LDH genes (ldhD and ldhL, respectively) and production of d-(−)- and l-(+)-lactic acid were studied in Lactobacillus helveticus CNRZ32. In order to develop a host for production of pure l-(+)-isomer of lactic acid, two ldhD-negative L. helveticus CNRZ32 strains were constructed using gene replacement. One of the strains was constructed by deleting the promoter region of the ldhD gene, and the other was constructed by replacing the structural gene of ldhD with an additional copy of the structural gene (ldhL) of l-LDH of the same species. The resulting strains were designated GRL86 and GRL89, respectively. In strain GRL89, the second copy of the ldhL structural gene was expressed under the ldhD promoter. The two d-LDH-negative strains produced only l-(+)-lactic acid in an amount equal to the total lactate produced by the wild type. The maximum l-LDH activity was found to be 53 and 93% higher in GRL86 and GRL89, respectively, than in the wild-type strain. Furthermore, process variables for l-(+)-lactic acid production by GRL89 were optimized using statistical experimental design and response surface methodology. The temperature and pH optima were 41°C and pH 5.9. At low pH, when the growth and lactic acid production are uncoupled, strain GRL89 produced approximately 20% more lactic acid than GRL86.